Hydrophobic surface modification of FMSS and its application as effective sorbents for oil spill clean‐ups and recovery. Issue 9 (7th May 2017) - Oribayo, Oluwasola; Pan, Qinmin; Feng, Xianshe; Rempel, Garry L.
Abstract : Superhydrophobic sponge‐like materials are attracting more attention in recent years as potential sorbent materials for oil spill clean‐up. In this work, the authors report the incorporation of hydrophobic structural features into a superhydrophilic pristine formaldehyde‐melamine‐sodium bisulfite copolymer sponge (FMSS) by N‐acylation with a fatty acid derivative, for use as an oil sorbent in oil spill clean‐ups. This resulted in our ability to transform the surface properties of the sponge skeleton to superhydrophobic with a contact angle of 143°. The acylated FMSS (a‐FMSS) was shown to retain the interconnected porous structure, and was characterized with microscopic and spectroscopic analyses. Sorption experiments with engine oil and chloroform showed that a‐FMSS had a very high oil sorption capacity (amounting to 99 and 168.2 times its own weight respectively) than commercial nonwoven polypropylene sorbent. In this view, a‐FMSS is considered to be a promising oil sorbent for potential applications in large‐scale oil spill clean‐ups. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4090–4102, 2017